Comparison of the Glaesserella parasuis Virulence in Mice and Piglets - Qi, Baichuan; Li, Feiyue; Chen, Kunpeng; Ding, Wenwen; Xue, Yun; Wang, Yang; Wang, Hongwei; Ding, Ke; Zhao, Zhanqin (Frontiers in Veterinary Science, 2021)
Abstract: In this study, we compared the virulence of the most common serovars of Glaesserella parasuis in China, serovars 4, 5, 12, and 13 (36 strains in total) in BALB/c mice and piglets. In mice, the median lethal doses (LD50s) of the four serovars were roughly 9.80 × 107 – 4.60 × 109 CFU, 2.10 × 108 – 8.85 × 109 CFU, 4.81 × 107 – 7.01 × 109 CFU, and 1.75 ×108 – 8.45 × 108 CFU, respectively. Serovar 13 showed the strongest virulence, followed by serovar 4, serovar 12, and serovar 5, but a significant difference in virulence was only observed between serovars 5 and 13. The virulence of strains of the same serovars differed significantly in piglets. Virulent and attenuated strains were present in all serovars, but serovar 5 was the most virulent in piglets, followed by serovars 13, 4, and 12. A significant difference in virulence was observed between serovars 5 and 4 and between serovars 5 and 12. However, the virulence of serovars 5 and 13 did not differ significantly. This comprehensive analysis of G. parasuis virulence in mice and piglets demonstrated that: 1) the order of virulence of the four domestic epidemic serovars (from strongest to weakest) in piglets was serovars 5, 13, 4, and 12; 2) both virulent and attenuated strains were present in all serovars, so virulence did not necessarily correlate with serovar; 3) Although G. parasuis was fatal in BALB/c mice, its virulence is inconsistent with that in piglets, indicating that BALB/c mice are inadequate as an alternative model of G. parasuis infection.